ANALYSIS OF ENTREPRENEURSHIP IN UKRAINE - HARVAT, Olha (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the number of active business entities by industry affiliation and territorial location over the past 10 years. The trends of entrepreneurial activity specific to each industry by territorial characteristics and for the country’s economy as a whole have been determined. The analysis was carried out taking into account the data of the Global Entrepreneurship Monitor program. Today, entrepreneurship is becoming the main activity of the majority of the country’s population, and it is the connecting link between society and the state that allows domestic economic entities to overcome barriers to access to world markets in order to maintain the national economy in conditions of martial law. The purpose of the article is to analyze and assess the current state of entrepreneurial activity in Ukraine based on a study of the number of active business entities by branch of the national economy in terms of territorial units, and based on the data obtained to make a forecast of the number of business entities as of the end of 2023. Thus, the total growth in the quantity of business entities in the reporting year 2022 compared to the previous year 2021 was 659027 units, the growth in the quantity of individual entrepreneurs was 49061 units or 3.1%, and the growth in the quantity of legal entities was 609926 or 164,4%. There was no significant drop in the value of the entrepreneurial activity indicator by types of economic activity. As a result of the analysis, it can be noted that the level of entrepreneurial activity of business entities not only has a tendency to increase, but an anticipatory growth relative to the last 10 years of the study. And this is in the conditions of war. Moreover, the growth in the number of business entities that we observe during the reporting year of 2022 can only be explained by the action of the law of synergy. After all, when forecasting the number of business entities for 2022, for example, based on the extrapolation method, it was possible to focus on the growth of the total number of business entities to 1981752 units or their increase in absolute terms by 25432 units. Instead, we have an increase of 659,027 units or 33.7%. However, we assume that by the end of 2023, the growth in the level of entrepreneurial activity will fall within the limits established by the extrapolation method, and will amount to 1.3% growth.